Abdominal wall movements predict intra-abdominal pressure changes in rats: a novel non-invasive intra-abdominal pressure detection method - Vincent, Deirdre; Mietzsch, Stefan; Braun, Wolfgang; Trochimiuk, Magdalena; Reinshagen, Konrad; Boettcher, Michael (Children, 2023)
(1) Background: As increases in intra-abdominal pressure (IAP) result in irreversible tissue damage, monitoring IAP in critically ill patients using the common urinary bladder catheter method is essential. However, this method can result in complications and is not suitable for very low birth weight neonates. The aim of this study was to establish a non-invasive and accurate method to detect IAP changes using an animal model. (2) Methods: IAP changes via intra-abdominal air application (up to 20 mmHg) were measured in 19 Wistar rats via an intra-abdominally placed intracranial pressure probe. Concurrently, abdominal surface tension was measured using a Graseby capsule (GC). (3) Results: A high correlation between abdominal wall distension and IAP (r = 0.9264, CI 0.9249-0.9279) was found for all subjects. (4) Conclusions: IAP changes in rats can be detected non-invasively using a GC. However, further studies are necessary to assess whether IAP changes can be measured using a GC in the neonatal population.
Gesehen am 04.04.2024